Environmental Science: Processes & Impacts - Environmental Science: Processes & Impacts (Royal Society of Chemistry, 2026)
Environmental Science: Processes & Impacts  publishes high quality papers and innovative perspectives that advance the understanding of chemical processes in the environment and their resulting impacts. The journal publishes research in all areas of the environmental chemical sciences, interfacing with earth science, applied science, and policy solutions.
FI 0.83
Q1
Keywords: Earth; Space & Environmental Sciences; Environmental Chemistry; Química ambiental; Acuerdos transformativos; Transformative agreements; Ciencias químicas ambientales; Procesos químicos en el ambiente e impactos asociados; Evaluación de contaminantes y riesgos para ecosistemas y salud humana